Efek Penambahan Kefir Sebagai Probiotik pada Ayam Boiler terhadap Panjang Usus - fanani, anhar faisal; Qulubi, M Hadziq; Andari, Gardis (Universitas Musamus, Merauke, Papua, 2020)
This study was to examine the effect of changes in digestive tract that is seen from the length of the small intestine size of broiler chickens given kefir. The study used 200 MB of broiler DOC as many as 200 animals which were kept randomly in a cage plot. The study was conducted for 5 weeks with 4 treatments and repeated 5 times so that the number of experimental units was 20 units. The treatments to be tested were: T0 = basal ration (control), T1 = basal ration + 1.5% probiotic, T2 = basal ration + 3% probiotic, T3 = basal ration + 4.5%. Kefir used was derived from goat milk which was given 10% kefir grain fermented for 48 hours. The data obtained were analyzed for variance based on a completely randomized design and continued using duncan test. The results showed that the final body weight was significantly different (P <0.05), while the feed efficiency, relative length of duodenum, jejunum, ileum, overall small intestine and cecum had no significant effect (P> 0.05). The conclusion that the administration of probiotics in the form of kefir has no significant effect on the relative length of the small intestine and cecum, but has a significant effect on final body weight. The use of kefir needs to be considered in terms of cost because it uses milk as a fermentation media.